The fallout of forgiveness: How forgiveness predicts third-party perceptions of the forgiver and the forgiver's relationships. (June 2015) - DiDonato, Theresa E.; McIlwee, Laurette J.; Carlucci, Marianna E.
Forgiveness within romantic relationships may have broader consequences. Two studies investigated how forgiveness decisions predict outsiders' perceptions of individuals and their relationships. Study 1 ( n = 364) used an experimental between-subject design and hypothetical vignettes to manipulate forgiveness, offense severity, and offense frequency. As hypothesized, participants perceived forgiving targets as more committed and satisfied, and the relation between forgiveness and person perceptions depended on offense frequency (competence) and severity (competence and warmth). In Study 2, participants ( n = 134) recalled friends' offenses. Forgiveness predicted perceived commitment, satisfaction, investment, warmth, and competence, at times interacting with severity and frequency, while accounting for intent and apologies. The findings are discussed in light of the importance of perceptions and social networks.